The Effect of Marketing Mix, Elements of Product, Price, Place, Promotion, People, Process, and Physical Evidence on Patient Satisfaction At Ananda Srengat Hospital Blitar - Ratih Dwinanda Pitaloka; Eric Harianto (Dinasti International Journal of Education Management And Social Science, 2025)
The healthcare industry in Indonesia is increasingly competitive, prompting hospitals to adopt effective marketing strategies to improve patient satisfaction. RSU Ananda Srengat-Blitar, as a Type C hospital that continues to grow, faces challenges in maintaining service quality and competitiveness in the midst of intense competition. This study aims to analyze the effect of marketing mix elements (Product, Price, Place, promotion, person, process, and physical evidence) on patient satisfaction at Ananda SRENGAT hospital-Blitar. Using a quantitative approach with Partial Least Square-Structural Equation Model (PLS-SEM) method, data were collected from 300 hospital patient respondents. The results of the analysis showed that the variables of physical evidence, price, people (HR), and service processes have a significant positive influence on patient satisfaction. Meanwhile, product, promotion, and venue variables have no significant influence. The recommendations of this study include improving the quality of physical facilities, transparency of service costs, training of medical personnel, and optimization of administrative systems. With the right strategy implementation, Ananda hospital can improve patient satisfaction and strengthen its competitiveness in the healthcare industry.